Virulence and Stress Responses of Shigella flexneri Regulated by PhoP/PhoQ - Lin, Zhiwei; Cai, Xia; Chen, Mingliang; Ye, Lina; Wu, Yang; Wang, Xiaofei; Lv, Zhihui; Shang, Yongpeng; Qu, Di (Frontiers in Microbiology, 2018)
The two-component signal transduction system PhoP/PhoQ is an important regulator for stress responses and virulence in most Gram-negative bacteria, but characterization of PhoP/PhoQ in Shigella has not been thoroughly investigated. In the present study, we found that deletion of phoPQ (△phoPQ) from Shigella flexneri 2a 301 (Sf301) resulted in a significant decline (reduced by more than 15-fold) in invasion of HeLa cells and Caco-2 cells, and less inflammation (- or +) compared to Sf301 (+++) in the guinea pig Sereny test. In low Mg2+ (10 μM) medium or pH 5 medium, the △phoPQ strain exhibited a growth deficiency compared to Sf301. The △phoPQ strain was more sensitive than Sf301 to polymyxin B, an important antimicrobial agent for treating multi-resistant Gram-negative infections. By comparing the transcriptional profiles of △phoPQ and Sf301 using DNA microarrays, 117 differentially expressed genes (DEGs) were identified, which were involved in Mg2+ transport, lipopolysaccharide modification, acid resistance, bacterial virulence, respiratory and energy metabolism. Based on the reported PhoP box motif [(T/G) GTTTA-5nt-(T/G) GTTTA], we screened 38 suspected PhoP target operons in S. flexneri, and 11 of them (phoPQ, mgtA, slyB, yoaE, yrbL, icsA, yhiWX, rstA, hdeAB, pagP and shf–rfbU-virK-msbB2) were demonstrated to be PhoP-regulated genes based on electrophoretic mobility shift assays and β-galactosidase assays. One of these PhoP-regulated genes, icsA, is a well-known virulence factor in S.flexneri. In conclusion, our data suggest that the PhoP/PhoQ system modulates S. flexneri virulence (in an icsA-dependent manner) and stress responses of Mg2+, pH and antibacterial peptides.